Design Optimization and Application of Hybrid Bit to Reduce a Well Cost in Geothermal Field - Fathaddin, Muhammad Taufiq; Andika, Fakhri Ade; Sitaresmi, Ratnayu (Journal of Earth Energy Engineering, 2020)
Hybrid bit is one of the innovations developed for very hard and abrasive formations such as in geothermal field. This bit eliminates the risk of losing cones, reduces tripping time, and increaseas ROP to reduce the well cost. The stage of data processing by calculating the UCS formation using D-BOS software and design optimization based on 9-7/8" bits simulations in granodiorite formations. The 1st phase was to determine the 4 best out of 7 hybrid bit designs that were selected from the highest ROP obtained, the most stable cutter cutting force, and the lowest vibration by comparing the results of FEA modeling of 1 ft drilling simulation. The 2nd phase is to choose 1 of the best from the 4 selected by doing 50 ft of drilling dynamics simulation which is assessed by directional capability, the durability, and the lowest MSE. In this study to improve drilling optimization in geothermal field, it was found that the Z616 hybrid bit design was the most optimal one. Based on 1st phase simulation, this bit was able to produce ROP of 6.38 mph, a stable cutter cutting force, very low average lateral 2.109 g and axial vibration 0.329 g. Furthermore, for the 2nd phase simulation of 50 ft, seen from the comparison of directional capability, this bit has a 0.91 deg/100 ft DLS in rotating mode, and 6.5 deg/100ft DLS in sliding mode means quite stable when drilling in rotary mode and easy to make some angle in slide mode. By its durability, the average value of lateral acceleration is 10 g, and the lateral force is 6 klbf. By MSE side, this bit also produces the lowest average MSE value of 769 psi. From the economic view, this bit can save USD 198,625 - USD 564,712 of a well cost.